2012
DOI: 10.1016/j.jaac.2011.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Proposed DSM-5 Criteria for Autism Spectrum Disorder

Abstract: Objective The primary aim of the present study was to evaluate the validity of proposed DSM-5 criteria for Autism Spectrum Disorder (ASD). Method We analyzed symptoms from 14,744 siblings (8,911 ASD; 5,863 non-ASD) included in a national registry, the Interactive Autism Network. Youth aged 2–18 were included if at least one child in the family was diagnosed with ASD. Caregivers reported symptoms using the Social Responsiveness Scale and the Social Communication Questionnaire. The structure of autism symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
248
2
15

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(287 citation statements)
references
References 61 publications
22
248
2
15
Order By: Relevance
“…The key difference is that those with a clinical diagnosis of ASD cross a threshold beyond which functioning is significantly impaired, whereas those high on ALTs but without a clinical diagnosis of ASD remain able to cope with the social interaction demands of society (Lundstro¨m et al 2012). This hypothesis has been addressed by examining the latent distribution of ASD measures across those with and without ASD using taxometric or latent class analysis methods, with the evidence at present pointing to ASD as a distinct category from ALTs (Frazier et al 2010(Frazier et al , 2012. Again, this line of research depends on measuring autistic traits in individuals without a clinical diagnosis of ASD.…”
Section: Introductionmentioning
confidence: 99%
“…The key difference is that those with a clinical diagnosis of ASD cross a threshold beyond which functioning is significantly impaired, whereas those high on ALTs but without a clinical diagnosis of ASD remain able to cope with the social interaction demands of society (Lundstro¨m et al 2012). This hypothesis has been addressed by examining the latent distribution of ASD measures across those with and without ASD using taxometric or latent class analysis methods, with the evidence at present pointing to ASD as a distinct category from ALTs (Frazier et al 2010(Frazier et al , 2012. Again, this line of research depends on measuring autistic traits in individuals without a clinical diagnosis of ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of early vocalisations for building sensorimotor links, this may offer some explanation for the early language and babbling deficits of ASC; although, notably, 11 Though we do recognise changes to nosology: DSM-IV (APA, 2000) had a three-factor model specifying impairments in the domains of 'social interaction', 'communication' (involving language criteria) and restricted and repetitive behaviours and interests, but DSM-5 combines the first two factors into a single factor called 'social communication'. The two-factor model better fits the symptom presentation of people with autism (Frazier et al, 2012;Mandy, Charman, & Skuse, 2012). This downplaying of language symptoms implies that these are no longer an essential aspect of diagnosis, but in fact, gold-standard diagnostic tools, the ADOS-G (Lord et al, 2000) and the ADI-R (Le Couteur et al, 2003), have not been yet adapted to the new DSM criteria and so language abnormalities (such as pronoun reversal and many more) remain central to diagnosis.…”
mentioning
confidence: 99%
“…There has been some concern in recent publications on the implications of these changes, especially related to the more stringent ASD diagnostic criteria [5], but some positive aspects have also been identified [6]. Field studies have shown that for autism and ADHD, clinicians in general agree with which patients meet DSM-5 diagnostic criteria; though, for some other conditions there is less agreement [7].…”
Section: • Exemplification Of Criteria: Criteria Just Mentioned Notmentioning
confidence: 99%